Diphenyleneiodonium enhances P2X7 dependent non-opsonized phagocytosis and suppresses inflammasome activation via blocking CX43-mediated ATP leakage. (April 2021) - Zhu, Yuanfeng; Chen, Xiaoli; Lu, Yongling; Fan, Shijun; Yang, Yongjun; Chen, Qian; Huang, Qianying; Xia, Lin; Wei, Yan; Zheng, Jiang; Liu, Xin
Abstract: The beneficial effects of antioxidants against oxidative stress have been well described. However, the pharmacological impacts of antioxidants other than inhibiting the production of reactive oxygen species (ROS) remain less understood. This study demonstrated that diphenyleneiodonium (DPI), a canonical NADPH oxidase 2 (NOX2) inhibitor, effectively promoted non-opsonized bacterial phagocytosis. Indeed, DPI abrogated the elevation in the extracellular ATP level of Escherichia coli ( E. coli ) -infected murine peritoneal macrophages, thereby restoring the association of the purinergic receptor P2X7 with non-muscle myosin heavy chain 9 (MYH9) to upregulate the P2X7 -dependent phagocytosis of E. coli . DPI also suppressed inflammasome activation and reduced necroptosis in E. coli -infected macrophages by decreasing extracellular ATP levels. Mechanistically, DPI upregulated p38 MAPK phosphorylation to suppress the expression and activity of the hemichannel protein connexin 43 (CX43), leading to the inhibition of CX43-mediated ATP efflux in E. coli -infected macrophages. In a murine E. coli infection model, DPI effectively reduced ATP release, decreased bacterial load and inhibited inflammasome activation, thereby improving survival and ameliorating organ injuries in model mice. In summary, our study demonstrates a previously unknown function of DPI in conferring protection against bacterial infection and suggests a putative antimicrobial strategy of modulating CX43 -dependent ATP leakage. Graphical Abstract: ga1